Regional Associations of Cortical Superficial Siderosis and β-Amyloid-Positron-Emission-Tomography Positivity in Patients With Cerebral Amyloid Angiopathy - Finze, Anika; Wahl, Hannes; Janowitz, Daniel; Buerger, Katharina; Linn, Jennifer; Rominger, Axel; Stöcklein, Sophia; Bartenstein, Peter; Wollenweber, Frank Arne; Catak, Cihan; Brendel, Matthias (Frontiers in Aging Neuroscience, 2022)
Objective A cross-sectional study to evaluate whether β-amyloid-(Aβ)-PET positivity and cortical superficial siderosis (cSS) in patients with cerebral amyloid angiopathy (CAA) are regionally colocalized. Methods Ten patients with probable or possible CAA (73.3 ± 10.9 years, 40% women) underwent MRI examination with a gradient-echo-T2*-weighted-imaging sequence to detect cSS and 18F-florbetaben PET examination to detect fibrillary Aβ. In all cortical regions of the Hammers atlas, cSS positivity (MRI: ITK-SNAP segmentation) and Aβ-PET positivity (PET: ≥ mean value + 2 standard deviations of 14 healthy controls) were defined. Regional agreement of cSS- and Aβ-PET positivity was evaluated. Aβ-PET quantification was compared between cSS-positive and corresponding contralateral cSS-negative atlas regions. Furthermore, Aβ-PET quantification of cSS-positive regions was evaluated in voxels close to cSS and in direct cSS voxels. Results cSS- and Aβ-PET positivity did not indicate similarity of their regional patterns, despite a minor association between the frequency of Aβ-positive patients and the frequency of cSS-positive patients within individual regions (rs = 0.277, p = 0.032). However, this association was driven by temporal regions lacking cSS- and Aβ-PET positivity. When analyzing all composite brain regions, Aβ-PET values in regions close to cSS were significantly higher than in regions directly affected with cSS (p < 0.0001). However, Aβ-PET values in regions close to cSS were not different when compared to corresponding contralateral cSS-negative regions (p = 0.603). Conclusion In this cross-sectional study, cSS and Aβ-PET positivity did not show regional association in patients with CAA and deserve further exploitation in longitudinal designs. In clinical routine, a specific cross-sectional evaluation of Aβ-PET in cSS-positive regions is probably not useful for visual reading of Aβ PETs in patients with CAA.